2013
DOI: 10.1590/s1516-18462013000500016
|View full text |Cite
|
Sign up to set email alerts
|

Triagem auditiva neonatal: índice de passa/falha com relação a sexo, tipo de parto e tempo de vida

Abstract: OBJETIVO: verificar em recém-nascidos (RNs) sem risco de perda auditiva o índice de passa/falha na Triagem Auditiva Neonatal Universal (TANU), relacionando-o com o sexo, o tipo de parto e o tempo de vida. MÉTODO: caracteriza-se como um estudo quantitativo, retrospectivo, transversal e de grupo, inserido na atenção secundária à saúde do hospital universitário onde foram analisados 1.526 prontuários de RNs, com analisador de Emissões Otoacústicas Transientes (EOAT) modelo Otoport Lite. Adotou-se como critério de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
3
1
0
2
Order By: Relevance
“…Differently, in the CRSA the "pass" result rate was approximately 86.0%, corroborating with other studies that report data from 75.6 to 88.3% (18)(19)(20) , as well as referral for follow-up due to RIHL 0.3% and diagnosis 4.8%…”
Section: Discussionsupporting
confidence: 89%
“…Differently, in the CRSA the "pass" result rate was approximately 86.0%, corroborating with other studies that report data from 75.6 to 88.3% (18)(19)(20) , as well as referral for follow-up due to RIHL 0.3% and diagnosis 4.8%…”
Section: Discussionsupporting
confidence: 89%
“…Although the sample was homogeneous, there was a higher number of male individuals concurring with other studies 14,15 .…”
Section: Discussionsupporting
confidence: 89%
“…Test failure rate was comparable to that reported in another study, performed in four maternities in Paraná, that found 5%, 3% and 2% in three of the institutions (data were not presented in the last) 10 , but lower than presented in studies conducted in secondary-level maternities, which found 11.7% and 25.3% 9,11 .…”
Section: Discussionsupporting
confidence: 86%